(untitled) (The International Journal for Scientific Research, 2024)
This work deals with removal of some pollutants from waste water, the rate of oxidation of some organic pollutants in water, such as phenol, cresol, toluene that have been oxidized by the reaction with polyoxometals catalyst to activate H2O2. have been investigated. The polyoxometals that were used, 10-molybdovanado sodium phosphate Na5Mo10VPO40 (HMoVPA) and 12-molybdophosphoric acid H3PMo12O40 (HMoPA). These reactions have been studied kinetically by varying the reactants concentrations, temperature, catalyst concentrations, pH and solvent. The rate of reaction was found to increase with an increase in concentration of pollutants, H2O2, and catalyst and temperature. Toluene appeared to have the highest value of rate constant, while paranitrophenol showed to have the lowest. In addition, Hammet equation was used to study the effect of the presence of electron donating group (- CH3), and withdrawing groups (- NO2, -Cl). Electron donating group increases the rate of reaction while electron withdrawing groups have the reverse effect. Reaction rate ρ was calculated (-1.97) for heterogeneous H3PMo12O24 catalyst and (-1.24) for homogeneous catalyst Na5Mo10V2PO40. Eyring equation was also used to calculate the enthalpy of activation ΔH# and the entropy of activation ΔS# for these reactions (34.323 KJmol-1 and -101.3 KJmol-1 for heterogeneous catalyst and 41.67 KJmol-1 and -78.57 KJmol-1 for homogenous catalyst respectively). H3PMo12O24 has the lowest value of ΔH#, which means that it is the most reactive catalyst while Na5Mo10V2PO40 is the lowest reactive among the catalysts studied.